Iridoid glycosides from the root of Acanthus sennii - Etagegnehu Assefa; Israel Alemayhu; Milkyas Endale; Fikre Mammo (GarVal Editorial Ltda., 2016)
Context: Acanthus sennii is a plant traditionally used for the treatment of antifungal, cytotoxic, anti-inflammatory, antipyretic, antioxidant, insecticidal, hepatoprotective, immunomodulatory, anti-platelet aggregation and anti-viral potential. Aims: To investigate the phytochemical constituents of roots of Acanthus sennii. Methods: Phytochemical screening tests were conducted to identify the class of compounds present in the root extract. Silica gel column chromatographic technique was applied to separate the constituents of the extracts. Various spectroscopic techniques (IR, 1H NMR, 13C NMR, DEPT-135, COSY, gHSQC, and gHMBC) were applied to determine the structures of isolated compounds. Results: Phytochemical screening of the dichloromethane/methanol (1:1) and methanol (100%) root extract of the plant revealed the presence of phenolic compounds, steroids, flavonoids, and terpenes. Chromatographic separation of dichloromethane/methanol (1:1) root extract of Acanthus sennii yielded two iridoid glycosides (1, 2). Conclusions: The roots of Acanthus senni contain various class of constituents such as flavonoids, phenols, terpenoids, tannins, and iridoid glycosides identified through phytochemical screening test and purification process, which might be responsible for the traditional use of the plant. To the best of our knowledge, these compounds are isolated for the first time from this genus.